Effectiveness of mind mapping as a learning tool among dental students - Mohnish Muchhal; Basavaraj Patthi; Ashish Singla; Ritu Gupta; Ravneet Malhi; Devanshu Chaudhary (Wolters Kluwer Medknow Publications, 2018)
Introduction: The foremost goal of our education system is to develop the students' skills to reach information rather than transferring the present information. Instead of understanding and applying the concepts (meaningful learning), students used to memorize the facts. Therefore, long-term independent learning process is required for the students. Aim: This study aims to evaluate the effectiveness of mind mapping as a learning tool and to assess its information retrieval potential among dental students over conventional system of learning. Materials and Methods: An interventional study was conducted among 90 students of BDS 3rd year students. A questionnaire consisting of questions related to oral hygiene index (OHI) and OHI-simplified (OHI-S) was distributed to them. Data were analyzed using Statistical Package for Social Sciences (SPSS) 18.0 (SPSS Inc., Chicago, IL, USA) and descriptive and analytical tests including mean, standard deviation, and Chi-square test. Results: Of the 90 students, only 82 students responded to the questionnaire generating a response rate of 89.5%. The mean score of students in the mind map (MM) group was significantly higher than the conventional group (posttest - 13.60 ± 0.99 vs 8.73 ± 2.13, P = 0.001). Gain in knowledge score was 7.74 vs. 3.43; statistically significant difference was found between the two groups for the gain in knowledge score as well as in mean percentage gain in knowledge score. Conclusion: Specific and prudent thinking with self-efficacy should be the purpose of education system rather than making the students literate only. This requires shifting of traditional teaching method with innovative method, and MM is one of the innovative as well as attractive processes of teaching which further help the students to learn the subject more effectively in a creative way.